Psychological well-being model - Ismail, Fadillah; Loo, Szi Ting; Abdul Kadir, Adibah; Mustafa, Siti Aisyah (Penerbit UTHM, 2020)
In past ten years, there is a rapid growing interest for negative experiences of psychological issues for instance depression, trauma and anxiety (Seligman & Csikszentmihalyi, 2000). However, the promotion of well-being is compulsory as the comprehensive health accepted as including physical, mental and social well-being (Kirkwood, Bond, May, & McKeith, 2010). Thus, the extend research on psychology well-being has been observed (Huppert, 2009; Ryff & Singer, 2006).